2021
DOI: 10.1136/bmjpo-2020-000881
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health in preschool children with underweight, overweight or obesity: a regional cohort study

Abstract: ObjectiveTo examine if underweight (UW), overweight (OW) or obesity (OB), or body mass index (BMI) expressed as its SD score (BMI SDS), were associated with psychological difficulties in preschool children.DesignRegional cohort study.SettingOppland County, Norway.MethodsAt the routine school entry health assessment at 5–6 years of age, parents were invited to participate by local public health nurses. The parents completed questionnaires on sociodemographic, health and lifestyle factors of the child and the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…
Studies by Donkor, Anderson, Cimino, and Mackenbach underscore the interconnectedness between abnormal weight and psychological issues during the time of measurement in young children. [4][5][6][7] Cimino also confirmed this association in their future years, with permanently
…”
supporting
confidence: 54%
See 2 more Smart Citations
“…
Studies by Donkor, Anderson, Cimino, and Mackenbach underscore the interconnectedness between abnormal weight and psychological issues during the time of measurement in young children. [4][5][6][7] Cimino also confirmed this association in their future years, with permanently
…”
supporting
confidence: 54%
“…17 The increased risk of being underweight in our population compared to the general population, is in line with previous studies, confirming the relation between underweight and psychological symptoms and eating behaviours, like emotional undereating, satiety responsiveness and fussiness of children. 4,18 Most of the tall children were also overweight. This is consistent with the theory of growth acceleration by increased levels of insulin and insulin-like growth factor-1 in children with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important clinical and public health problem among children and adolescents associated with adverse health outcomes at all stages of human life and may reflect food poverty (Ieiri et al 2021), unhealthy eating habits (Rawal et al 2021), or an increased risk of many diseases. Underweight children and adolescents are more likely to suffer from infectious diseases (Goutines et al 2021), have reduced cognitive functions (Suryawan et al 2021), mental disorders (Donkor et al 2021;Zeiler et al 2021) and have low scores your health (Linardon et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to girls, most studies found boys to be more at risk of developing emotional and behavioural problems [ 14 , 15 , 16 ]. Many studies have highlighted socioeconomic status or household income as a significant factor associated with emotional and behavioural problems in preschool [ 17 , 18 , 19 ]. Lower household income frequently correlates with higher levels of socioeconomic stress and hardship, which can lead to a less caring and nurturing environment for children.…”
Section: Introductionmentioning
confidence: 99%